Agile Project Management For Dummies - Layton, Mark C. (John Wiley & Sons, 2012)
Be flexible and faster with Agile project management As mobile and web technologies continue to evolve rapidly, there is added pressure to d evelop and implement software projects in weeks instead of months. Agi le Project Management For Dummies can make that happen. This is the fi rst book to provide a simple, step–by–step guide to Agile Project Mana gement approaches, tools, and techniques. With the fast pace of mobile and web technology development, software project development must kee p pace; Agile Project Management enables developers to complete and im plement projects more quickly and this book shows you how. Offers a pr actical context for understanding and applying Agile techniques, movin g from theory into actual practice Explains when to use Agile and how to avoid common pitfalls Written by experts who know how to apply the principles in real–world situations Agile Project Management For Dummi es enables you to understand and apply Agile principles for faster, mo re accurate development.